UP CLOSE NOBODY IS NORMAL! - Moreira, Fabiana Wanderley de Souza; de Araújo, Georgia Daniella Feitosa; de Oliveira Neto, Aristides José (Seven Editora, 2025)
The article criticizes pedagogical and discursive practices that stigmatize people with disabilities in the school environment, creating a "culture of the disabled" that leads to academic failure. Inspired by the mythology of Procrustes, it highlights how these normalizing practices exclude and hierarchize, reinforcing a "perverse Darwinism." In the 20th century, medical-psychological discourse, influenced by movements such as the hygienists, shaped Special Education, segregating those who were "different." Beginning in the 1980s, the pedagogical perspective gained strength, promoting inclusion, citizenship, and respect for subjectivities. However, the text questions whether these changes have overcome exclusion, warning of the persistence of normalizing discourses. DOI: https://doi.org/10.56238/sevened2025.030-002